Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Get quick and reliable solutions to your questions from a community of seasoned experts on our user-friendly platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Sure! Let's solve the given linear equation step-by-step and verify the result.
The equation is:
[tex]\[ \frac{4m + 3}{7} + 2 = \frac{m + 5}{2} \][/tex]
### Step 1: Eliminate the fractions
To eliminate the fractions, we can multiply every term by the least common multiple (LCM) of the denominators. The denominators are 7 and 2, so the LCM is 14.
Multiply every term by 14:
[tex]\[ 14 \cdot \left(\frac{4m + 3}{7}\right) + 14 \cdot 2 = 14 \cdot \left(\frac{m + 5}{2}\right) \][/tex]
This simplifies to:
[tex]\[ 2(4m + 3) + 28 = 7(m + 5) \][/tex]
### Step 2: Distribute and simplify both sides
Distribute the constants inside the parentheses:
[tex]\[ 2 \cdot 4m + 2 \cdot 3 + 28 = 7 \cdot m + 7 \cdot 5 \][/tex]
This simplifies to:
[tex]\[ 8m + 6 + 28 = 7m + 35 \][/tex]
Combine like terms:
[tex]\[ 8m + 34 = 7m + 35 \][/tex]
### Step 3: Isolate the variable
To isolate [tex]\(m\)[/tex], subtract [tex]\(7m\)[/tex] from both sides:
[tex]\[ 8m - 7m + 34 = 35 \][/tex]
This simplifies to:
[tex]\[ m + 34 = 35 \][/tex]
Now, subtract 34 from both sides:
[tex]\[ m = 35 - 34 \][/tex]
This gives:
[tex]\[ m = 1 \][/tex]
### Step 4: Verify the solution
Substitute [tex]\(m = 1\)[/tex] back into the original equation to verify it satisfies the equation:
[tex]\[ \frac{4(1) + 3}{7} + 2 = \frac{1 + 5}{2} \][/tex]
Simplify inside each fraction:
[tex]\[ \frac{4 + 3}{7} + 2 = \frac{6}{2} \][/tex]
So,
[tex]\[ \frac{7}{7} + 2 = 3 \][/tex]
This simplifies to:
[tex]\[ 1 + 2 = 3 \][/tex]
Indeed, [tex]\(3 = 3\)[/tex] is true.
Therefore, the solution to the equation is:
[tex]\[ m = 1 \][/tex]
And we have verified that this value satisfies the original equation.
The equation is:
[tex]\[ \frac{4m + 3}{7} + 2 = \frac{m + 5}{2} \][/tex]
### Step 1: Eliminate the fractions
To eliminate the fractions, we can multiply every term by the least common multiple (LCM) of the denominators. The denominators are 7 and 2, so the LCM is 14.
Multiply every term by 14:
[tex]\[ 14 \cdot \left(\frac{4m + 3}{7}\right) + 14 \cdot 2 = 14 \cdot \left(\frac{m + 5}{2}\right) \][/tex]
This simplifies to:
[tex]\[ 2(4m + 3) + 28 = 7(m + 5) \][/tex]
### Step 2: Distribute and simplify both sides
Distribute the constants inside the parentheses:
[tex]\[ 2 \cdot 4m + 2 \cdot 3 + 28 = 7 \cdot m + 7 \cdot 5 \][/tex]
This simplifies to:
[tex]\[ 8m + 6 + 28 = 7m + 35 \][/tex]
Combine like terms:
[tex]\[ 8m + 34 = 7m + 35 \][/tex]
### Step 3: Isolate the variable
To isolate [tex]\(m\)[/tex], subtract [tex]\(7m\)[/tex] from both sides:
[tex]\[ 8m - 7m + 34 = 35 \][/tex]
This simplifies to:
[tex]\[ m + 34 = 35 \][/tex]
Now, subtract 34 from both sides:
[tex]\[ m = 35 - 34 \][/tex]
This gives:
[tex]\[ m = 1 \][/tex]
### Step 4: Verify the solution
Substitute [tex]\(m = 1\)[/tex] back into the original equation to verify it satisfies the equation:
[tex]\[ \frac{4(1) + 3}{7} + 2 = \frac{1 + 5}{2} \][/tex]
Simplify inside each fraction:
[tex]\[ \frac{4 + 3}{7} + 2 = \frac{6}{2} \][/tex]
So,
[tex]\[ \frac{7}{7} + 2 = 3 \][/tex]
This simplifies to:
[tex]\[ 1 + 2 = 3 \][/tex]
Indeed, [tex]\(3 = 3\)[/tex] is true.
Therefore, the solution to the equation is:
[tex]\[ m = 1 \][/tex]
And we have verified that this value satisfies the original equation.
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.